Electron inelastic mean free path at energies below 100 eV. (24th April 2017) - Nguyen-Truong, Hieu T
Abstract: Knowledge of electron inelastic mean free paths (IMFPs) is important for electron spectroscopy and microscopy studies. Here, we determine the IMFPs at energies below 100 eV for 10 elemental solids (V, Fe, Ni, Mo, Pd, Ag, Ta, W, Pt, and Au) within the dielectric formalism, using the energy-loss function calculated in the adiabatic local-density approximation of time-dependent density-functional theory. The resulting IMFPs at a few eV above the Fermi energy are comparable to those from ab initio calculations in the GW approximation of many-body theory. The present approach provides an alternative to evaluate hot-electron inelastic lifetimes.